Wind Power Generation by Compressed Air Energy Storage (CAES) Technology - Saxena, Saurabh; Ali, Maroof; Kamal, Mustafa (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Wind energy is clean, ecofriendly, safe non conventional energy resource. Energy storage systems are increasingly gaining importance with regard to their role in achieving load leveling, especially for matching intermittent sources of renewable energy with customer demand, as well as for storing excess nuclear or thermal power during the daily cycle. Compressed air energy storage (CAES), with its high reliability, economic feasibility, and low environmental impact, is a promising method for large-scale energy storage. Although there are only two large-scale CAES plants in existence, recently, a number of CAES projects have been initiated around the world, and some innovative concepts of CAES have been proposed. Existing CAES plants have some disadvantages such as energy loss due to dissipation of heat of compression, use of fossil fuels, and dependence on geological formations. This paper reviews the main drawbacks of the existing CAES systems and presents some innovative concepts of CAES. The scope of this paper is to simply create a methodology for wind power generation using the compressed air energy storage system